(untitled) (Religious dialogue and cooperation, 2025)
Globalization has accelerated cultural exchange but also intensified competition, fueling wars, climate crises, disasters, and cyber threats that heighten global anxiety. In response, this paper explores conscience-centered peace practices rooted in Tai Ji Men, a qigong and martial arts Menpai with a long tradition of spiritual cultivation. Drawing from over two decades of personal practice, the study highlights how prayer, martial arts, and qigong can foster inner calmness, moral action, and collective resilience. Special attention is given to the Bell of World Peace and Love, a global cultural initiative through which world leaders have pledged to uphold conscience and harmony. The paper also examines the Tai Ji Men case, a prolonged legal and human rights controversy in Taiwan, as a litmus test for freedom of belief and cultural diversity. Through analysis of lived experience, international engagement, and the broader human rights discourse, the study argues that conscience awakening and cultural-spiritual practices can generate nonviolent, resilient forces for peace. Ultimately, resolving structural injustices such as the Tai Ji Men case is essential not only for Taiwan’s democratic development but also for strengthening global solidarity and advancing sustainable peace.”